Factors associated with adverse COVID-19 outcomes in patients with psoriasis – insights from a global registry-based study (2020)
Background: The multi-morbid burden and use of systemic immunosuppressants in people with psoriasis may confer greater risk of adverse COVID-19 outcomes but data are limited. Objective: Characterize the course of COVID-19 in psoriasis and identify factors associated with hospitalization. Methods: Clinicians reported psoriasis patients with confirmed/suspected COVID-19 via an international registry, PsoProtect. Multiple logistic regression assessed the association between clinical/demographic characteristics and hospitalization. A separate patient-facing registry characterized risk-mitigating behaviours. Results: Of 374 clinician-reported patients from 25 countries, 71% were receiving a biologic, 18% a non-biologic and 10% no systemic treatment for psoriasis. 348 (93%) fully recovered from COVID-19, 77 (21%) were hospitalized and nine (2%) died. Increased hospitalization risk was associated with older age (multivariable-adjusted OR 1.59 per 10 years, 95% CI 1.19-2.13), male sex (OR 2.51, 95% CI 1.23-5.12), non-white ethnicity (OR 3.15, 95% CI 1.24- 8.03) and comorbid chronic lung disease (OR 3.87, 95% CI 1.52-9.83). Hospitalization was more frequent in patients using non-biologic systemic therapy than biologics (OR 2.84, 95% CI 1.31-6.18). No significant differences were found between biologic classes. Independent patient-reported data (n=1,626 across 48 countries) suggested lower levels of social isolation in individuals receiving non-biologic systemic therapy compared to biologics (OR 0.68, 95% CI 0.50-0.94). Conclusion: In this international moderate-severe psoriasis case series, biologics use was associated with lower risk of COVID-19-related hospitalization than non-biologic systemic therapies, however further investigation is warranted due to potential selection bias and unmeasured confounding. Established risk factors (being older, male, non-white ethnicity, comorbidities) were associated with higher hospitalization rates.